The extent of violence inflicted on adolescent Aboriginal girls in the Northern Territory - Susan Moore; John R. Condon; Vincent YF He; Kylie Stothers; Tamika Williams; Steven Guthridge (BMC Public Health, 2022)
Abstract Background Australian Aboriginal and Torres Strait Islander women are at very high risk of violence but there is little evidence about the age at which their higher exposure to violence commences. The aim of this study was to investigate violence inflicted on Aboriginal girls during childhood and adolescence, relative to Aboriginal boys and non-Aboriginal girls. Methods This was a retrospective cohort study using de-identified administrative data for NT residents aged 0-17 years. This study used linked hospital and child protection data to investigate hospitalization for injury caused by assault and substantiated child maltreatment involving violence (physical and sexual abuse). Results The incidence of assault hospitalization and substantiated physical/sexual abuse was much higher for Aboriginal than non-Aboriginal adolescents but similar for girls and boys to about age ten, then increased much more for Aboriginal girls than boys. In the 14-17 age-group, assault hospitalization incidence was 125% higher for Aboriginal girls than boys but 56% lower for non-Aboriginal girls than boys. 4.6% of Aboriginal girls were hospitalized (30.9% more than once) for assault between twelfth and eighteenth birthdays, compared to 3.4% of Aboriginal boys and 0.3% of non-Aboriginal girls. The incidence of assault hospitalization during adolescence was over three times higher for Aboriginal children who had substantiated child maltreatment during childhood. Conclusion The very high levels of violence suffered by Aboriginal women commence in the pre-teen years. Non-Aboriginal girls are ‘protected’ from the rising levels of violence that boys experience as they progress through adolescence, but Aboriginal girls are not afforded such protection.